Alkynamide phthalazinones as a new class of TbrPDEB1 inhibitors. Issue 18 (15th September 2019) - de Heuvel, Erik; Singh, Abhimanyu K.; Edink, Ewald; van der Meer, Tiffany; van der Woude, Melanie; Sadek, Payman; Krell-Jørgensen, Mikkel P.; van den Bergh, Toine; Veerman, Johan; Caljon, Guy; Kalejaiye, Titilola D.; Wijtmans, Maikel; et al.
Graphical abstract: Abstract: Several 3′, 5′-cyclic nucleotide phosphodiesterases (PDEs) have been validated as good drug targets for a large variety of diseases. Trypanosoma brucei PDEB1 (TbrPDEB1) has been designated as a promising drug target for the treatment of human African trypanosomiasis. Recently, the first class of selective nanomolar TbrPDEB1 inhibitors was obtained by targeting the parasite specific P-pocket. However, these biphenyl-substituted tetrahydrophthalazinone-based inhibitors did not show potent cellular activity against Trypanosoma brucei (T. brucei) parasites, leaving room for further optimization. Herein, we report the discovery of a new class of potent TbrPDEB1 inhibitors that display improved activities against T. brucei parasites. Exploring different linkers between the reported tetrahydrophthalazinone core scaffold and the amide tail group resulted in the discovery of alkynamide phthalazinones as new TbrPDEB1 inhibitors, which exhibit submicromolar activities versus T. brucei parasites and no cytotoxicity to human MRC-5 cells. Elucidation of the crystal structure of alkynamide 8b (NPD-048) bound to the catalytic domain of TbrPDEB1 shows a bidentate interaction with the key-residue Gln874 and good directionality towards the P-pocket. Incubation of trypanosomes with alkynamide 8b results in an increase of intracellular cAMP, validating a PDE-mediated effect in vitro and providing a new interesting compound series for further studies towards selective TbrPDEB1 inhibitors with potent phenotypic activity.